The role of neighborhood disadvantage in predicting mortality in patients after transcatheter aortic valve replacement. Issue 6 (14th July 2021) - Goitia, Jesse; Phan, Derek Q.; Lee, Ming‐Sum; Moore, Naing; Mansukhani, Prakash; Aharonian, Vicken; Brar, Somjot S.; Zadegan, Ray
Abstract: Background: Neighborhoods have a powerful impact on health. Prior investigations into disparities associated with transcatheter aortic valve replacement (TAVR) have focused on race and access to the procedure. We sought to investigate the role of neighborhood disadvantage on mortality post‐TAVR. Methods: Patients who underwent TAVR at Kaiser Permanente Los Angeles Medical Center between June, 2011 and March, 2019 were evaluated. Neighborhood disadvantage was defined using the area deprivation index, an established and validated index that considers multiple socioeconomic metrics. Cutoffs used for disadvantage were national percentile ≥25% and state decile ≥6. Cox proportional hazards regression analysis was used to assess outcomes. Results: A total of 668 patients (age 82.1 ± 7.5 years, 49% female) were included, of which 215 (32.2%) were from disadvantaged neighborhoods by state decile, and 167 (25%) by national percentile. At a median follow‐up of 18.8 months (interquartile range 8.7–36.5 months), neighborhood disadvantage was independently associated with increased all‐cause mortality (National percentile: hazard ratio [HR] 1.91, 95% confidence interval [CI] 1.35–2.69; state decile: HR 1.68, 95% CI 1.21–2.34). On propensity scored analysis, neighborhood disadvantaged remained independently associated with increased all‐cause mortality (National percentile: IPTW HR 1.86, 95% CI 1.52–2.28, PSM HR 1.67, 95% CI 1.11–2.51; state decile: IPTW HR 1.55, 95% CI 1.26–1.91, PSM HR 2.0, 95% CI 1.33–2.99). Conclusion: Living in a disadvantaged neighborhood was independently associated with increased mortality post‐TAVR on multivariate and propensity score matched analysis. Further investigations into the role of neighborhood disadvantage are needed to address disparities and improve outcomes post‐TAVR.